Differences in Types of Stigma Between Demographic Groups Among College Students With Food Insecurity - Vollmer, Rachel L., PhD, RD; Drake, Teresa, PhD, MCHES, RD; Reed, Sokonie, DNP (Journal of nutrition education and behavior, 2025)
AbstractObjectiveCompare stigma constructs across demographic and student characteristics among food-insecure college students. MethodsThis cross-sectional study recruited college students with food insecurity to complete an online survey to report food security status, food insecurity-related stigma (personalized stigma, disclosure concerns, negative self-image, and public attitudes), and demographic characteristics. One-way analysis of variance and independent t tests were used to assess differences in stigma. ResultsSeventy-seven students with food insecurity completed the online survey. First-generation students with very low food security reported higher disclosure concerns than students with marginal/food security (F[2,73] = 3.16, P = 0.05) and non-first-generation students (t[74] = −1.99, P = 0.05), respectively. White students reported less personalized stigma than non-White students (t[72] = 2.01, P = 0.04). Conclusions and ImplicationsThis research identifies groups of students who may have higher disclosure stigma and past stigmatizing experiences.